2004
DOI: 10.1590/s0034-72992004000200017
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculose e blastomicose laríngeas: relato de três casos e revisão de literatura

Abstract: Resumo / SummaryAs doenças granulomatosas da laringe apresentam quadros polimórficos de difícil diagnóstico pelo exame clínico. São patologias que apresentam evolução favorável se o tratamento efetivo for introduzido precocemente, evitando complicações. Muitas vezes, a primeira manifestação destas patologias dá-se a nível da laringe, portanto devem ser lembradas no diagnóstico diferencial de doenças inflamatórias. Relatamos o caso de três pacientes que procuraram nosso Serviço com queixa de disfonia, sem alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 10 publications
0
13
0
2
Order By: Relevance
“…Therefore, pulmonary TB is the dominant form. Other pathways, may, however, be conduits, such as the digestive system, skin, tonsils, eye and others that might have direct contact with the aggressor agent [7].…”
Section: Transmissionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, pulmonary TB is the dominant form. Other pathways, may, however, be conduits, such as the digestive system, skin, tonsils, eye and others that might have direct contact with the aggressor agent [7].…”
Section: Transmissionmentioning
confidence: 99%
“…One of the organs that can be secondarily affected by TB is the larynx, even although in some cases, laryngeal TB may have a primary involvement [7].…”
Section: Laryngeal Tbmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the granulomatous diseases of the larynx, tuberculosis is the most common. It is estimated that the involvement of the larynx occurs around 1% of patients with pulmonary tuberculosis (7). A study in Denmark showed a prevalence of 0.8% of laryngeal involvement in patients with tuberculosis and those patients with laryngeal involvement, 100% had pulmonary tuberculosis (10).…”
Section: Introductionmentioning
confidence: 99%
“…The most common site of involvement is the laryngeal vocal fold (50-70%), followed by ventricular band (40-50%) and the remaining 10-15% may involve the epiglottis, aryepiglottic fold, arytenoids, posterior commissure and subglottis ( 7). Laryngeal involvement usually occurs as edematous lesion, which subsequently ulcer at the posterior commissure arytenoid, and is classically associated with extensive pulmonary tuberculous lesions (7). Predominates in males, with approximate ratio of male / female 9:1 (10).…”
Section: Introductionmentioning
confidence: 99%